2018
DOI: 10.19080/ctftte.2018.04.555642
|View full text |Cite
|
Sign up to set email alerts
|

Use of Moringa (Moringa Stenopetala) Seed Extract for Removal of Some Anionic Dyes (Direct and Reactive Dyes) in Textile Wastewater

Abstract: With textile wastewater being one of the most sources of pollution containing higher value of colour, BOD, COD and several pollutants, brings serious problem to the ecological environment. This study is particularly focused on evaluating the efficacy of removal of dyes such as reactive dyes, direct dyes, mixture of dye wastes and mixture of industrial and dye wastewaters by the natural absorbent Moringa. The seeds of the Moringa tree contain a coagulant protein that can be used in the treatment of industrial w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…23 The seed kernels and dried leaves were ground into a medium-fine powder with a local mill to achieve solubilization of active ingredients in the seed. 26 These crushed kernels and leaves were sieved using a sieve size of <300 μm. 34 Then, the powders of the leaf and seed were packed in a small plastic bag separately for safety (as seen in Figure 2) and kept in the laboratory under an ambient temperature of 22°C to 25°C and stored in a desiccator to create and maintain a dry environment until treatment and analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…23 The seed kernels and dried leaves were ground into a medium-fine powder with a local mill to achieve solubilization of active ingredients in the seed. 26 These crushed kernels and leaves were sieved using a sieve size of <300 μm. 34 Then, the powders of the leaf and seed were packed in a small plastic bag separately for safety (as seen in Figure 2) and kept in the laboratory under an ambient temperature of 22°C to 25°C and stored in a desiccator to create and maintain a dry environment until treatment and analysis.…”
Section: Methodsmentioning
confidence: 99%
“…1 There are factors identified by different scientific researches like turbidity, pH, contact time, settling time, stirring time, temperature, and dosage/concentration that might affect the treatment efficiency of natural plants in reducing microbes or turbidity or heavy metals from water. 1,22,24,[26][27][28] The effect of turbidity, pH, settling time, temperature and dosage were considered in this study. Mixing/stirring time plus settling time is equal to contact time-based on this study.…”
Section: Introductionmentioning
confidence: 99%
“…These findings were in line with previous research findings, which revealed that treating water samples with MO seed cake reduced turbidity (Ghebremichael et al, 2005;Nand, 2012;Shan et al, 2017;Sotheeswaran et al, 2011). According to Govindan (2018), color and turbidity removal effectiveness of up to 98.4 percent and 84.3 percent respectively was achieved employing 70 mg/L coagulant extract of Moringa Stenopetala. Garde et al (2017) discovered that utilizing 0-0.4 g/L of coagulant dose resulted in 1-25 percent COD removal.…”
Section: Process Comparisonmentioning
confidence: 97%